Exposing illegal hunting and wildlife depletion in the world's largest tropical country through social media data - El Bizri, Hani R.; Oliveira, Marcela A.; Rampini, Aline Pessutti; Knoop, Simon; Fa, Julia E.; Coad, Lauren; Morcatty, Thais Queiroz; Massocato, Gabriel Favero; Desbiez, Arnaud L. J.; Campos-Silva, João Vitor; La Laina, Daniel Zani; Duarte, José Maurício Barbanti [UNESP]; et al. (Wiley, 2024)
Globally, illegal sport hunting can threaten prey populations when unregulated. Due to its covert nature, illegal sport hunting poses challenges for data collection, hindering efforts to understand the full extent of its impacts. We gathered social media data to analyze patterns of illegal sport hunting and wildlife depletion across Brazil. We collected data for 2 years (2018–2020) across 5 Facebook groups containing posts depicting pictures of illegal sport hunting events of native fauna. We described and mapped these hunting events by detailing the number of hunters involved, the number of species, the mean body mass of individuals, and the number and biomass of individuals hunted per unit area, stratified by Brazilian biome. We also examined the effects of defaunation on hunting yield and composition via regression models, rank–abundance curves, and spatial interpolation. We detected 2046 illegal sport hunting posts portraying the hunting of 4658 animals (∼29 t of undressed meat) across all 27 states and 6 natural biomes of Brazil. Of 157 native species targeted by hunters, 19 are currently threatened with extinction. We estimated that 1414 hunters extracted 3251 kg/million km2. Some areas exhibited more pronounced wildlife depletion, in particular the Atlantic Forest and Caatinga biomes. In these areas, there was a shift from large mammals and reptiles to small birds as the main targeted taxa, and biomass extracted per hunting event and mean body mass across all taxonomic groups were lower than in other areas. Our results highlight that illegal sport hunting adds to the pressures of subsistence hunting and the wild meat trade on Brazil's wildlife populations. Enhanced surveillance efforts are needed to reduce illegal sport hunting levels and to develop well-managed sustainable sport hunting programs. These can support wildlife conservation and offer incentives for local communities to oversee designated sport hunting areas.
Keywords: caza furtiva; caza recreativa; conservation culturomics; crímenes de fauna; culturomía de la conservación; defaunación; defaunation; especie amenazada; Facebook; overexploitation; poaching; recreational hunting; sobreexplotación; threatened species; wildlife crime